The Impact of the Development and Utilization of We-Media in the Internet Era on Urban Tourism - Peng, Peng; Jin, Yingxin; Gu, Jiaying (Journal of Global Economy, Business and Finance, 2024)
With the rapid development of the internet era, numerous online phenomena have emerged, among which We-Media stands as a highly representative entity. Leveraging its unique characteristics, We-Media continuously influences various aspects of our economy, politics, production, and daily life. Its impact on urban tourism development is particularly pronounced, bringing about changes that cannot be underestimated and benefits that are immeasurable. However, every coin has two sides. While bringing positive effects to cities, it also poses numerous challenges. This paper conducts an analytical study on the impact of We-Media utilization on urban tourism development and the corresponding measures to address the issues faced.